An Omni-Directional Wideband Patch Antenna with Parasitic Elements for Sub-6 GHz Band Applications - Liton Chandra Paul; Himel Kumar Saha; Tithi Rani; Md. Zulfiker Mahmud; Tushar Kanti Roy; Wang-Sang Lee (International Journal of Antennas and Propagation)
An omni-directional inset fed wideband microstrip patch antenna (MPA) for Sub-6 GHz applications has been presented. Initially, a slotted small patch antenna with a full ground plane is designed and then partial ground plane and electromagnetically coupled parasitic elements have been incorporated and optimized to get desired performance. The volume of the studied antenna is 40 × 40 × 1.575 mm3 having a partial ground plane. Rogers RT 5880 is used as the dielectric substrate tier. The simulated operating band of the MPA ranges from 2.67 GHz to 4.20 GHz, covering the N77 and N78 bands with a centre operating frequency of 3.29 GHz. The antenna can also be used for WiMAX rel 2 (3.4–3.6 GHz) applications. After fabrication and testing, the antenna also shows almost the same working band extending from 2.67 GHz to 4.15 GHz. The use of a partial ground plane plays a vital role in making it an omni-directional antenna, and the existence of a rectangular parasitic element in the ground plane influences the improvement of gain and directivity of the antenna. The designed MPA allows it to run as a wide band antenna with a good reflection coefficient profile, high average efficiency, and 1 < VSWR < 2. At a resonant tip of 3.29 GHz, the simulated gain and directivity are 3.16 dB and 3.38 dBi, respectively. The measured gain is slightly higher than the simulated gain. The computer simulation technology (CST) is used for modelling and exploring all the performance matrices of the antenna. The results of the fabricated prototype present very good similarity with the simulated results and both simulated and measured results also support the Sub-6 GHz band. The antenna prototype shows a very well balanced set of radiation characteristics with a miniaturized volume and high efficiency. Therefore, the inset fed MPA can be contemplated as a candid model for Sub-6 GHz band applications.